Hybrid Threats and Civil-Military Synergy: Strengthening National Resilience in the Era of Non-Traditional Security Challenges - Wilopo, Wilopo; Putri, Erti Fadhilah (Civil and Military Cooperation Journal, 2026)
The contemporary security landscape is increasingly shaped by hybrid threats that integrate military and non-military dimensions, including cyberattacks, disinformation, environmental crises, and pandemics. These complex and multidimensional threats challenge traditional state-centric security frameworks and demand integrated, adaptive, and multi-actor responses. This study examines the role of civil-military synergy in strengthening national resilience, with a specific focus on Indonesia as a disaster-prone and geopolitically strategic country. Employing a qualitative research design based on a systematic literature review and case-based analysis, this study develops a novel conceptual model, the Adaptive Civil-Military Resilience Framework (ACMRF). The findings reveal that while Indonesia has demonstrated strong operational collaboration between civilian institutions and the military, significant challenges persist in governance fragmentation, regulatory ambiguity, technological integration, and societal trust. The study contributes theoretically by advancing a systems-based and adaptive understanding of resilience, and practically by proposing policy pathways to enhance coordination, institutional capacity, and community engagement. The ACMRF model offers a dynamic and integrative framework for analyzing resilience in hybrid threat environments, with broader applicability to other developing and disaster-prone countries.